2016
DOI: 10.7150/jbji.16967
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas oryzihabitans Infected Total Hip Arthroplasty

Abstract: Pseudomonas oryzihabitans is a saprophytic gram-negative microorganism usually found in damp environments, only occasionally responsible for human pathology. Infection mainly occurs in malnourished, immunocompromised individuals with indwelling catheters. There is no previous published record of infection after joint arthroplasty. To enhance the literature, in this article we report a patient with a Pseudomonas oryzihabitans infected total hip arthroplasty, and discuss the diagnosis and management of this unus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Our patient was treated by piperacillin/tazobactam, imipenem, and ceftazidime. The former reports confirmed that imipenem and ciprofloxacin are the first therapeutic choices for P oryzihabitant infection …”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Our patient was treated by piperacillin/tazobactam, imipenem, and ceftazidime. The former reports confirmed that imipenem and ciprofloxacin are the first therapeutic choices for P oryzihabitant infection …”
Section: Discussionmentioning
confidence: 63%
“…We reported the first case of skin infection of P oryzihabitans in a patient with hidradenitis suppurativa; we isolated the bacterium as monomicrobial infection in which its potential pathogenicity can be approved in the case of cutaneous infection. Patients with diabetes mellitus are susceptible to various infections caused by opportunistic agents; review of the literatures shows that patients with immune deficiency are provided with the best condition to be infected with P oryzihabitans …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations